State estimation method development for SCADA and synchronized phasor measurements within power system - P. I. Bartolomey; S. I. Semenenko (Известия высших учебных заведений: Проблемы энергетики)
In  modern power systems, the special kind of measurement systems was actively implemented for the last 20 years. These measurement systems have a high-precision synchronized time stamp, which makes it possible to obtain, in addition to the effective value of line current and bus voltage, the electrical phase angles. In previous years, a large number of methods for obtaining a steady state based on telemetry (state estimation) have been formed, which are based on taking measurements of only the modules of these quantities, as well as the values of the active and reactive components of injection power in the nodes and flows in the branches. Most of these methods were based on the weighted least squares method, or other methods based on the maximum likelihood method, for which determination of the weighting factors of measurements, traditionally chosen on the basis of relative errors of these measurements, is required. However, there is the problem of taking measurements of electrical angles, for which the relative error is fundamentally indeterminable. There is also a problem associated with the integration of measurements of phasor measurements with traditional measurement tools into a single measuring system due to a significant difference in accuracy and update frequency. The paper proposes an approach for combining phasor measurements with traditional SCADA measurements in the framework of the state estimation procedure, taking into account the problems described.